Incidence of Newly Diagnosed Type 1 Diabetes Mellitus in Children and Adolescents in Henan Province of China from 2017 to 2020: A Retrospective Multicenter Study Based on Hospitalization Data - Qiong Chen; Na Xu; Yongxing Chen; Mingming Yan; Fengyan Tian; Wei Yang; Yan Cui; Ai Huang; Yangshiyu Li; He Zhang; Zhihong Jiang; Ruizhi Zheng; et al. (Galenos Yayincilik, 2022)
INTRODUCTION: The incidence of type 1 diabetes mellitus (T1DM) is rapidly increasing worldwide. However, the incidence in Henan Province of China has been unknown for more than two decades. This study aimed to estimate the incidence of T1DM in the 0.5-14.9 years age group in Henan Province of China from 2017 to 2020. METHODS: A retrospective analysis of hospital registration data from 18 cities in Henan Province, China, identified 1726 patients (843 males, 883 females) between 0.5-14.9 years of age with newly diagnosed T1DM in Henan Province from January 1st, 2017, to December 31st, 2020, covering more than 19 million children years at risk. RESULTS: The crude incidence of T1DM per 100 000 person years for the 0.5-14.9 years age group in the Henan Province of China was 2.19 [95% confidence interval (CI): 1.99, 2.40], with a peak in the 10-14.9 years age group. The rate ratio of females to males was 1.32 (95% CI: 1.20, 1.45) in the 0.5-14.9 years age group. The incidence rate was higher in females than males in the 5-9.9 years age group (p<0.01) and the 10-14.9 years age group (p<0.01). The seasonality of the incidence was different from that in previous reports, with the lowest incidence in the spring. DISCUSSION AND CONCLUSION: The incidence of T1DM in the 0.5-14.9 years age group in Henan Province was still among the lowest reported globally, but was in line with other incidence rates reported from China.